2000
DOI: 10.4012/dmj.19.65
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Antibacterial Agents to MMA-TBB Dentin Bonding Systems. Influence on Tensile Bond Strength and Antibacterial Effect.

Abstract: To produce a bonding system which has both high bond strength and antibacterial properties, an antibacterial agent (vancomycin: VCM or metronidazol: MN) was added to the PMMA powder of 4-META/MMA-TBB resin (CB). The influence of the addition of an antibacterial agent on tensile bond strength to dentin and the antibacterial effect were investigated in this study. Forty-seven freshly extracted bovine first or second incisors were used to measure the tensile bond strength to dentin. The bond strengths to bovine d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 12 publications
0
17
0
2
Order By: Relevance
“…The simplest way to develop composites and adhesives with antimicrobial effect, seems to be the addition of a soluble disinfectant, such as chlorhexidine [188][189][190], triclosan [191], quaternary ammonium compounds such as benzalconium chloride [192,195] and cetylpyridinium chloride [193], the antibacterial biopolymer chitosan [194], the antibiotics vancomycin and metronidazole [195] and epigallocatechin-3-gallate (EGCG) (the major polyphenol present in green tea) [196] to the resin matrix. However, all soluble compounds added to composites tend to show so-called 'burst effect', i.e.…”
Section: Xxxe13mentioning
confidence: 99%
“…The simplest way to develop composites and adhesives with antimicrobial effect, seems to be the addition of a soluble disinfectant, such as chlorhexidine [188][189][190], triclosan [191], quaternary ammonium compounds such as benzalconium chloride [192,195] and cetylpyridinium chloride [193], the antibacterial biopolymer chitosan [194], the antibiotics vancomycin and metronidazole [195] and epigallocatechin-3-gallate (EGCG) (the major polyphenol present in green tea) [196] to the resin matrix. However, all soluble compounds added to composites tend to show so-called 'burst effect', i.e.…”
Section: Xxxe13mentioning
confidence: 99%
“…3,4 As the contemporary dentine adhesive systems have not proved completely effective in eliminating microleakage at tooth/restoration interface, the incorporation of antibacterial agents into these materials has been proposed in an attempt to prevent caries recurrence. [5][6][7][8][9][10][11][12][13][14][15] Among the antibacterial agents incorporated into adhesive materials, the resin monomer 12-methacryloyloxydodecylpyridinium bromide, known as MDPB, stands out. 8,9,13 The main advantage of MDPB is its capacity to copolymerize with other resin monomers being immobilised within the polymer matrix, which confers safety and prolonged antibacterial action to this agent, as it does not leach to the medium.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators have reported attempts to inhibit plaque accumulation on the surfaces of teeth and restorations with the use of antibacterial varnishes or resin materials containing antibacterial agents. [8][9][10][11] The incorporation of chlorhexidine into glass-ionomer cements produced antibacterial activity. 12 An experimental antibacterial bonding system (Ku-raray, Osaka, Japan) combined with Transbond XT (3M Unitek, Monrovia, Calif) was evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Kudou et al 11 demonstrated that the incorporation of vancomycin and metronidazole into 4-META/MMA-TBB resin achieved a strong antibacterial effect against Streptococcus mutans (S mutans). Kazuno et al 14 reported that MMA/TBB resin containing newly developed amphiphilic lipids showed a strong antibacterial effect against S mutans or Streptococcus sobrinus.…”
Section: Introductionmentioning
confidence: 99%